Pelvic abscess in a sexually inactive teenage girl: a case report and review of literature - Anant, Monika; Sinha, Kajal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Pelvic abscess, a potentially life-threatening collection of infected exudate in pelvic organs, commonly occurrs in sexually active women having pelvic inflammatory disease due to sexually transmitted infections. It is rare to find it in a girl never engaged in sexual activity. The index case was a of pelvic abscess in a 15year virgin girl. She presented with fever abdominal pain and lump. Ultrasonography suggested a complex pelvic mass but on CT imaging pelvic abscess was confirmed. She underwent surgical intervention after failed medical treatment to drain the collection and preservation of internal genital organs. Pelvic abscesses demand prompt diagnosis and management to prevent further complications and long-term poor fertility outcomes specially at young age and should be a differential diagnosis in girls with pain abdomen and fever.